Concordance Level between Impulse Oscillometry and Spirometry for Pulmonary Function Test - Hapsari, Brigitta Devi Anindita; Melita , Melita; Siregar, Sihsusetyaningtyas Tiominar; Apriningsih, Hendrastutik; Adhiputri, Artrien (Jurnal Respirologi Indonesia, 2025)
Background: The most widely used lung function test, spirometry, requires constant coaching and more effort. An alternative modality of impulse oscillometry (IOS) was introduced, which is simpler than spirometry, requiring only basic tidal breathing and less cooperation, but with less stringent standards. Methods: This research was a diagnostic test research with medical records data of patients who underwent spirometry and oscillometry procedures within the same period. The study was conducted in Sebelas Maret University General Hospital from March to September 2024. Results: A total of 77% of examinations gave the same results, namely restriction in 32 people (30.8%) and obstruction in 48 people (46.2%). Meanwhile, as many as 23% of IOS examinations gave different results compared to spirometry examinations (discordance). Six normal results from spirometry showed the impression of obstruction in IOS. The agreement between the IOS examination and spirometry was moderately significant (P=0.0001). Conclusion: Impulse oscillometry is a useful adjunct to spirometry, which is still the gold standard, especially for patients who are incapable of performing forced maneuvers.